2021
DOI: 10.31234/osf.io/94csh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

As Within, so Without; As Above, so Below: Common Mechanisms Can Support Between- and Within-Trial Learning Dynamics

Abstract: Two fundamental difficulties when learning is deciding 1) what information is relevant, and 2) when to use it. To overcome these difficulties, humans continuously make choices about which dimensions of information to selectively attend to, and monitor their relevance to the current goal. Although previous theories have specified how observers learn to attend to relevant dimensions over time, those theories have largely remained silent about how attention should be allocated on a within-trial basis, which dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…By fitting AARM to eye-tracking data in previous work, we were able to show that AARM's mechanisms of attention not only predict learning at the level of response accuracy, but at the level of information sampling behaviors as well with increasing reliance on relevant dimensions as the task proceeds. Additional work showed that AARM extends to within-trial dynamics, such that it can accurately predict the order in which individuals will fixate to dimensions after gaining sufficient experience with the structure of the task (Weichart et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By fitting AARM to eye-tracking data in previous work, we were able to show that AARM's mechanisms of attention not only predict learning at the level of response accuracy, but at the level of information sampling behaviors as well with increasing reliance on relevant dimensions as the task proceeds. Additional work showed that AARM extends to within-trial dynamics, such that it can accurately predict the order in which individuals will fixate to dimensions after gaining sufficient experience with the structure of the task (Weichart et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…increased categorization accuracy across trials) is conceptualized as a natural consequence of storing experiences of stimuli and associated feedback as they occur, and preferentially allocating attention to the most relevant dimensions. Here, we will introduce the framework in terms of three core components: Representation, Decision, and Attention (Turner, 2019;Weichart et al, 2021).…”
Section: Adaptive Attention Representation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accepted that problem-solving is based on the construction of simplified representations of the problem under consideration, which reduce the dimensions needed to solve the problem. These simplified initial representations bias where attention is to be initially committed and refocused in the process, interchanging between covert attention to a goal hierarchy and overt attention to information changing online (Weichart et al, 2022). They also affect the value of representations, balancing the cost of action plans with their utilities (Ho et al, 2022).…”
Section: Integrated Cognition-personality-school Performance Modelmentioning
confidence: 99%